Pemberdayaan Masyarakat melalui Sosialisasi Pembuatan Pupuk Organik Cair Berbasis Limbah Rumah Tangga untuk Meningkatkan Kualitas Lingkungan dan Produktivitas Tanaman di Desa Jayapura, Kabupaten Siak - Sari, Efilda; Andrikasmi, Sukamarriko; Dewita, Salsa Gading; Saputra, Wijaya; Ramadhani, Syakirah; Sitanggang, Dina Sesilia BR; Diyandra, M. Zaky; Silalahi, Yohana Elfrida; Andika, Restu; Panjaitan, Ribka Mattathiah; Pratama, Mario Aji; Somayani, Somayani; Fadillah, Farhan Marsha (Unri Conference Series: Community Engagement, 2025)
Ineffective household waste management is often the cause of environmental pollution and public health problems. One applicable solution is processing household organic waste into liquid organic fertilizer (LOF), which is beneficial for plants and environmentally friendly. This community service program will be conducted in Jayapura Village, Bungaraya District, Siak Regency, with the aim of empowering the community to convert organic waste into valuable products. The method used is a participatory approach through socialization, training, and hands-on practice in making LOF. The results of this community service showed high enthusiasm from the participants during all stages of the activity. The training participants were able to understand the LOF production process well and began to apply it independently in their home gardens. In addition to producing useful fertilizer, this activity also has the potential to reduce the amount of waste disposed into the environment. The benefits of this program are not only experienced individually but also collectively through the creation of a healthier and more productive environment. This activity is expected to serve as a model for the application of simple, practical technology, strengthen environmental awareness, and encourage community independence in supporting sustainable household agriculture.